Sectoral dynamics and environmental quality in Côte d‘Ivoire: assessing the impact of structural transformation - Jeffrey Kouton; Johan Didier Kakou; Yann Muriel Okoua (Cogent Economics & Finance, 2024)
As global consumption patterns continue to exert unprecedented pressure on ecological systems, the urgent need for sustainable development frameworks has become increasingly evident. This study explores the critical intersection of structural transformation and environmental quality within the context of Côte d‘Ivoire, as the country navigates its National Development Plan aimed at structural transformation. Specifically, this research explores how structural changes across the agricultural, industrial, and service sectors impact environmental quality in Côte d‘Ivoire. Employing a Nonlinear Autoregressive Distributed Lag (NARDL) model, it investigates the asymmetric effects of sectoral contributions to the Gross Domestic Product (GDP) on the ecological footprint, distinguishing between positive and negative shocks during the period 1961–2021. The findings reveal that positive changes in the agricultural sector’s share reduce the ecological footprint by 0.222% in the long term, with no significant short-term impact. Conversely, a 1% negative shock in the sector results in a 0.391% increase in the ecological footprint in the short term. For the industrial sector, a 1% increase in its share leads to a 0.178% reduction in the ecological footprint over the long term, while negative shocks show no significant impact. The service sector demonstrates a positive environmental outcome, where a 1% increase in value-added reduces the ecological footprint by 0.368% in the long term and by 0.288% in the short term. For policymakers, these results highlight the importance of promoting sustainable practices within the agricultural and industrial sectors to achieve long-term environmental goals in Côte d’Ivoire. These results are critical for the implementation of Côte d‘Ivoire’s National Development Plan, which emphasizes the important role of agriculture and industry in its economic transformation, while addressing environmental sustainability.